Islam and entrepreneurship: The role of Islamic banking - Mohammad Reza Farzanegan; Ahmed Badreldin (Philipps-University Marburg, School of Business and Economics, 2022)
Studies on the relationship between religion and Entrepreneurship suggest that Islam discourages entrepreneurship. This is sometimes used to explain the excessively high unemployment figures for Muslim majority countries. However, we argue that studies that support this claim have missed a critical moderating factor, namely the presence of Shariah-compliant financing through Islamic banks. Using a multivariate regression analysis of 69 countries, our research shows empirically that the negative effect of Islam on entrepreneurship only applies in the absence of Shariah-compliant access to finance. This negative effect disappears in the presence of Islamic banks, thus disproving the generalized claim that Islam discourages entrepreneurship and showing that Muslim majority countries with high unemployment would do well to encourage the establishment of Shariah-complaint modes of financing to allow inclusion of religious entrepreneurs who would otherwise be excluded from the economy.
Keywords: 330; Islam; Entrepreneurship; Islamic Finance; Islamic Banking; Financial development; NewBusiness Formation; Shariah